THE RELATIONSHIP BETWEEN SELF-ESTEEM AND SUBJECTIVE WELL-BEING AMONG OSTEOARTHRITIS PATIENTS: A CROSS-SECTIONAL STUDY - Imamatul Faizah; Ratna Yunita Sari; Riska Rohmawati; Siti Nur Hasina; Rahmadaniar Aditya Putri (Universitas Nahdlatul Ulama Surabaya, 2026)
Background: Osteoarthritis is a degenerative joint disease that has a significant impact on quality of life, particularly among the elderly. In addition to pain and physical limitations, individuals with osteoarthritis also experience a decline in self-esteem and subjective well-being.Purpose: This study aims to analyze the relationship between self-esteem and subjective well-being among patients with osteoarthritis in Surabaya Community Health Center.Methods: This study employed a correlational analytic design with a cross-sectional approach. The study population consisted of 30 respondents, with a sample of 28 selected using simple random sampling. The independent variable in this study was self-esteem, and the dependent variable was subjective well-being. The instruments used were the Rosenberg Self-Esteem Scale and the Satisfaction with Life Scale. Data analysis was performed using the Spearman rank test with a significance level of α = 0.005.Results: The results of this study showed that the majority (60.7%) of individuals with osteoarthritis had high self-esteem, and nearly half (35.7%) had a high level of subjective well-being. The statistical analysis indicated a significant relationship (ρ value < 0.001). Therefore, self-esteem is associated with subjective well-being among individuals with osteoarthritis.Conclusion: There is a significant relationship between self-esteem and subjective well-being in the Wonokromo Community Health Center area. The results of this study are expected to encourage individuals with high subjective well-being to continue maintaining high self-esteem by accepting themselves as they are, engaging in active social participation, and fostering an optimistic outlook on life.